Analyzing the Impact of International Trade on Indonesia's Economic Growth - Matondang, Khairani Alawiyah; Sinaga, Anisa Fitria; Lubis, Atika Atayarisah; Amelia, Regita (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
International trade is an arena where goods and services are exchanged on a global scale. This happens because various countries collaborate in trade, driven by the desire to circulate goods and services freely. Through international trade, a country can increase prosperity and create balance in demand, supply, and services. This research aims to analyze the impact of international trade on Indonesia's economic growth. The research method used is qualitative research using literature review, where the author will examine written sources from various library references by collecting data, reviewing and analyzing data obtained from these written sources. By conducting international trade, a country can experience e increased prosperity through economic growth, job creation, and increasing Gross Domestic Product (GDP). Additionally, international trade enables the transfer of technology and business knowledge. However, international trade can also have an impact on reducing domestic demand due to imports, which can reduce domestic productivity and employment opportunities and result in a decrease in economic growth.